Composição química e estabilidade termo-oxidativa de blends a base de óleo de palma (Elaeis guineenses) - Andrade, Mychelle de Lira (2020)
Palm oil (PO) or palm oil is extracted from the fruits of the palm Tree Elaeis guineensis Jacq. It has a high amount of saturated fatty acids, which gives it greater stability. Soybean (SO) and sunflower (SFO) oils, in turn, contain high amounts of unsaturated fatty acids, beneficial to health, however, are more susceptible to oxidation. Blends of oils with different properties are a simple alternative for the creation of new products, with improved properties compared to those presented by individual oils. Therefore, the objective of this study was to prepare blends of palm oil with soybean and sunflower oils and to evaluate them for their thermal and oxidative stability by accelerated methods and in the preparation of foods by frying in immersion. The oils were purchased commercially and evaluated for iodine, peroxide, acidity and saponification indices. The fatty acid profile was determined by Gas Chromatography coupled to Mass Spectrometer (GC-MS) and tocopherol content by High Efficiency Liquid Chromatography (HPLC). Blends with varying proportions of these oils, the same analyses were applied to pure oils and blends, with the exception of tocopherol analysis. The oils and blends were evaluated by Thermogravimetry, Rancimat and PetroOxy, in order to verify their thermal and oxidative stability. Soybean and sunflower oils were added with natural and synthetic antioxidants to compare their effect in relation to palm oil in blends. The thermal profile of oils and blends was also monitored in heating at 180 oC, during the intermittent period of 24 hours, the results were submitted to infrared spectroscopy (IR). The performance of oils and blends was also evaluated in the frying of frozen English potatoes type toothpick, also analyzed by IV and the results showed that the behavior of the blends in relation to sunflower oil, are more indicated for use in the frying of the toothpick potato, but compared to the behavior observed for palm oil, this would be the most appropriate choice. According to the results obtained, the nine blends improved the saturated/established ratio compared to PO, as well as had their oxidative induction periods increased in relation to those obtained for SO and SFO oils. The thermal evaluation of the blends showed that there was no influence of the percentage of palm oil on the formation of trans fatty acids, indicating safety for the consumer in the case of oils with higher levels of polyunsaturated fatty acids.